Disparate selection of mutations in the dihydrofolate reductase gene (dhfr) of Plasmodium ovale curtisi and P. o. wallikeri in Africa. - Jing Chen; Xiaoqin Ma; Jianxia Tang; Sui Xu; Yaping Gu; Feng Tang; Yuanyuan Cao; Weiming Wang; Huayun Zhou; Jiayao Zhang; Xinyu Yu; Guoding Zhu; et al. (Public Library of Science (PLoS), 2022)
Plasmodium ovale curtisi and P. ovale wallikeri are both endemic in sub-Saharan Africa, the Middle East and Southeast Asia. Molecular surveillance data for drug resistance in P. ovale spp. is limited at present. We analysed polymorphisms in the podhfr, pocrt and pocytb genes of P. ovale spp. in 147 samples collected from travelers returning to China from Africa. Two podhfr mutations, S58R and S113N/T were detected in P. ovale curtisi with high/moderate frequencies of 52.17% and 17.39%, respectively. Evidence of positive selection (dN/dS = 2.41) was found for podhfr in P. ovale curtisi and decreased diversity (He) of microsatellite markers flanking the mutant alleles suggests that selective sweeps have occurred for both. Mutations E34G (1.50%) and L43V (1.50%) in pocrt of P. ovale curtisi, and E34G (3.70%), I102M (1.80%) and V111F (1.80%) of P. ovale wallikeri were found at low frequencies. Mutations R66K (6.20%), R75K (11.63%) and R95K (3.88%) of pocytb were found in both P. ovale curtisi and P. ovale wallikeri. These results suggest that the podhfr gene of P. ovale curtisi may be subject to drug selection in Africa, warranting further attention. We observed significant differences in the prevalence and distribution of podhfr mutations between the two P. ovale species, suggestive of fundamental biological differences between them.